QUSHLARNING AGROTSENOZ LANDSHAFTIDA AHAMIYATI - Doniyorov, B.N; Ametov, Ya.I (MODERN PROBLEMS AND PROSPECTS FOR ORGANIZING A HEALTHY LIFESTYLE AND PROPER NUTRITION, 2024)
QUSHLARNING AGROTSENOZ LANDSHAFTIDA AHAMIYATI